Kestabilan Titik Keseimbangan Model Epidemik SVEIS dengan Saturated Incidence Rate - Mohammad Soleh (UIN Sultan Syarif Kasim Riau, 2018)
In this journal discusses about the SVEIS epidemic model with saturated incidence rate. SVEIS epidemic model divides the population into four copartements, namely S (susceptible), V (vaccinated), E (exposed), and I (infected). The methods used in this model are the eigen value criteria or the Routh-Hurwitz criteria. The results obtained from the analysis of models has two equilibrium point, there are disease free equilibrium point and the endemic equilibrium disease point. If the condition are complete, then a disease free equilibrium point and endemic equilibrium disease point are asymptotically stable. Keywords : Asymptotically stable, Equilibrium point , SVEIS epidemic model.